2021
DOI: 10.1186/s12879-021-06810-4
|View full text |Cite
|
Sign up to set email alerts
|

Creating symptom-based criteria for diagnostic testing: a case study based on a multivariate analysis of data collected during the first wave of the COVID-19 pandemic in New Zealand

Abstract: Background Diagnostic testing using PCR is a fundamental component of COVID-19 pandemic control. Criteria for determining who should be tested by PCR vary between countries, and ultimately depend on resource constraints and public health objectives. Decisions are often based on sets of symptoms in individuals presenting to health services, as well as demographic variables, such as age, and travel history. The objective of this study was to determine the sensitivity and specificity of sets of sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
6
1
Order By: Relevance
“…A significant portion of infected hospital workers tested positive before the initial recommended test date(s), which implied the benefit of the early test (and early detection) triggered by symptoms. This contrasts with other studies on symptomatic patients presenting at health services which demonstrated poor diagnostic accuracy of signs and symptoms [26,27]. An explanation might be that, in addition to being symptomatic, all of our included subjects must have certain exposure to an infected person.…”
Section: Discussioncontrasting
confidence: 74%
“…A significant portion of infected hospital workers tested positive before the initial recommended test date(s), which implied the benefit of the early test (and early detection) triggered by symptoms. This contrasts with other studies on symptomatic patients presenting at health services which demonstrated poor diagnostic accuracy of signs and symptoms [26,27]. An explanation might be that, in addition to being symptomatic, all of our included subjects must have certain exposure to an infected person.…”
Section: Discussioncontrasting
confidence: 74%
“…Unlike many other studies [ 6 8 , 10 , 16 ], this research examined the number of days that specific symptoms are reported within an infection episode. We found that PCR+ participants reported a significantly longer duration of specific symptoms per episode, compared with those that were PCR−; cough had the longest duration followed by tiredness whilst runny nose had the longest duration among PCR− participants.…”
Section: Discussionmentioning
confidence: 99%
“…MCA has been widely used in various studies, including cancer and COVID-19 studies. [19][20][21][22][23] The standardized score or z-score was calculated at each time point using the formula z = (x−μ)/σ, where x represents the raw value, μ represents the mean, and σ is the standard deviation.…”
Section: Discussionmentioning
confidence: 99%